2020
DOI: 10.1186/s12864-020-06825-2
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-sequencing reveals positional memory of multipotent mesenchymal stromal cells from oral and maxillofacial tissue transcriptomes

Abstract: Background: Multipotent mesenchymal stromal cells (MSCs) can be isolated from numerous tissues and are attractive candidates for therapeutic clinical applications due to their immunomodulatory and pro-regenerative capacity. Although the minimum criteria for defining MSCs have been defined, their characteristics are known to vary depending on their tissue of origin. Results: We isolated and characterized human MSCs from three different bones (ilium (I-MSCs), maxilla (Mx-MSCs) and mandible (Md-MSCs)) and proceed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Our previous study revealed that the osteogenic potential of MBMSCs was similar to that of iliac bone marrow-derived MSCs (IBMSCs); however, MBMSCs scarcely differentiated into adipocytes [5]. Consistent with our study, other groups have also reported that MBMSCs exhibit lower adipogenic differentiation potential than that exhibited by IBMSCs [7,10]. However, the mechanisms through which the differentiation of MBMSCs is regulated remain unclear.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our previous study revealed that the osteogenic potential of MBMSCs was similar to that of iliac bone marrow-derived MSCs (IBMSCs); however, MBMSCs scarcely differentiated into adipocytes [5]. Consistent with our study, other groups have also reported that MBMSCs exhibit lower adipogenic differentiation potential than that exhibited by IBMSCs [7,10]. However, the mechanisms through which the differentiation of MBMSCs is regulated remain unclear.…”
Section: Introductionsupporting
confidence: 89%
“…Most of the bone tissue is derived from the mesoderm, whereas the craniofacial bone, including the maxillary/mandibular bone, is derived from the neural crest [6]. MSCs isolated from the orofacial region and iliac crest have been reported to exhibit site-speci c characteristics owing to the differences in embryological origins [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the gene profiles in spheroids with different MSCs are somewhat consistent. In our previous transcriptome analysis of bone marrow-derived MSCs and PDL-derived MSCs, the expression of the HOX gene differed between the two MSCs [ 23 ]. In other words, MSCs derived from different anatomical sites have marked differences in gene expression and positional memory, although they meet the same general characterization criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For example, craniofacial bones are generated by neural crest-derived MSCs, but the axial and appendicular bones are derived from paraxial and lateral mesoderm (LM)-derived MSCs, respectively ( Olsen et al, 2000 ; Isern et al, 2014 ). Furthermore, maxilla-derived MSCs are negative for homeodomain transcription factor (HOX) gene expression, while ilium-derived MSCs highly express HOX genes and exhibit superior differentiation to chondrocytes compared with maxilla- and mandible-derived MSCs ( Matsubara et al, 2005 ; Onizuka et al, 2020 ), further suggesting that MSCs of different origins possess variable functions. The above evidence indicates that the functional heterogeneity of MSCs may be partially due to their undefined developmental origins.…”
Section: Introductionmentioning
confidence: 99%